PECULIARITIES OF THE REGIONAL BLOOD CIRCULATION IN THE PROCESS OF THE DENTAL IMPLANTS PLACEMENT ON THE LOWER JAW - Маланчук, В.О.; Ціленко, О.Л.; Грабовецький, П.В.; Grabovetskiy, V.I. (World of Medicine and Biology, 2012)
The report contains the information about the regional blood circulation in the process of dental implants placement with the possibility of exudates outflow at the surgery zone. Within the framework of the research fifty patients with the partial or full loss of teeth on the lower jaw have been examined and treated. It has been carried out a rheografic research for the purpose of blood circulation studying on the lower jaw before and after implantation.
Keywords: dental implant; bone tissue; osseointegration; surgical phase of implantation